2020
DOI: 10.2478/acph-2021-0009
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antioxidant and antityrosinase activities of Manilkara kauki

Abstract: Manilkara kauki L. Dubard is a tropical plant in the genus Manilkara of family Sapotaceae. This study investigated the total phenolic and flavonoid contents, and antioxidant and antityrosinase activities in different parts of M. kauki (fruits, leaves, seeds, stem barks and woods) and in fractions of stem barks. The total phenolic and flavonoid contents of the methanol and aqueous crude extracts of different parts of M. kauki ranged from 10.87 to 176.56 mg GAE (gallic acid equivalents) per gram of crude extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…Previous studies have also reported similar findings in which higher TFC than TPC was obtained (Srisupap & Chaicharoenpong, 2021;Ling et al, 2019). However, researchers have not found a more definitive explanation for why this phenomenon can occur and open the possibility of further research to find the cause.…”
Section: Total Phenolic and Flavonoid Contentsmentioning
confidence: 86%
“…Previous studies have also reported similar findings in which higher TFC than TPC was obtained (Srisupap & Chaicharoenpong, 2021;Ling et al, 2019). However, researchers have not found a more definitive explanation for why this phenomenon can occur and open the possibility of further research to find the cause.…”
Section: Total Phenolic and Flavonoid Contentsmentioning
confidence: 86%
“…Based on Srisupap and Chaicharoenpong, the methanol extract of Manilkara kauki stem barks showed the lowest IC 50 value of tyrosinase inhibition, 0.25 ± 0.03 mg/mL, followed by water extract of Manilkara kauki stem barks, 0.41 ± 0.01 mg/mL. 15 Overall, methanol extracts showed a lower IC 50 of tyrosinase inhibition compared with the water extracts. The same tyrosinase inhibitory trend was found in both extraction methods, which followed the order of stem barks > leaves > fruits > seeds, while woods showed no inhibitory activity at all.…”
Section: Acanthus Ilicifoliusmentioning
confidence: 89%
“…Viet et al reported the antityrosinase and antioxidant activities of Celastrus hindsii leaf extracts (α-amyrin and β-amyrin). 36 The tyrosinase inhibition IC 50 of α-amyrin and β-amyrin was 178.85 ± 3.28 μg/mL, while the IC 50 for positive control of kojic acid was 15 37 The results found that the leaves exhibited higher antityrosinase activities in both monophenolase and diphenolase assays with an inhibition IC 50 of 167 ± 18 and 70 ± 7 μg/mL, respectively, compared to the branches with tyrosinase monophenolase inhibition IC 50 of 268 ± 24 and 91 ± 8 μg/mL in a tyrosinase diphenolase assay. Similar results were found in the antioxidant assays, as leaves exhibited great DPPH and ABTS radical scavenging activities with IC 50 values of 78 ± 13 and 117 ± 16 μg/mL, respectively.…”
Section: Acanthus Ilicifoliusmentioning
confidence: 99%
See 2 more Smart Citations